Role of electrical resistivity method to identify fresh water aquifers in Nankana Sahib, Punjab, Pakistan - Shabbir, Haider; Butt, Nabeel Afzal; Zafar, Adeela; Mir, Muhammad Khalid (Journal of Himalayan Earth Sciences, 2020)
Groundwater assessment plays a crucial role for town planning and urbanization in an area. This research aims to delineate subsurface quality zones by using electric resistivity technique in Nankana Sahib area (31° 45′ 12″ 31° 25′ 1″ N; 73° 39′ 48″ 73° 55′ 30″) Tehsil of Lahore, Pakistan. Around 36 vertical electric sounding data points were collected using schlumberger electrode configuration. Depth of investigation is upto 180m. Inversion method is applied to convert apparent resistivity in to true resistivity of lithology. The true resistivity range of the various subsurface lithology’s is from 2.6 to 220 Ω.m. The results obtained from vertical electric sounding are matched and calibrated with borehole lithological data in the vicinity of study area indicates that resistivity < 25 ohm.m are considered as saline water zone in formation like clay and silt, 25-35 ohm.m brackish to marginal water zone information like clayey sand, silty sand and silt. Resistivity range from 35-55 ohm.m represents fresh water zone (low quality) in formation like sand (silty), and greater than 55 ohm.m represents fresh water, fine to coarse grained sand, gravels and cankers. Aquifers identified in the study area are sand dominant at depth interval of 0-30 m, 30-90 m and 90-180 m. subsurface lithology is chiefly sand with small clay lenses and aquifer is mostly dominant by marginal fresh water.